THE INFLUENCE CLARITY OF BUDGET TARGETS AND REPORTING SYSTEMS ON PERFORMANCE ACCOUNTABILITY OF BAUBAU CITY GOVERNMENT AGENCIES - Mustaqim, Fariz; Abdul Rakhman, La Ode; Pardana, Deki (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This study aims to analyze the effect of budget target clarity and reporting systems on the performance accountability of Baubau City government agencies. The population in this study is the Baubau City Government which consists of all local government organizations (OPD) in the city of Baubau, totaling 32 OPDs. each OPD has 3 respondents so that the sample in this study amounted to 96 respondents. The method used is quantitative descriptive analysis method using multiple linear regression. Based on the results of the study, it can be concluded that (1) budget target clarity affects the performance accountability of Baubau City government agencies, with a significance value of 0.000 <0.05; (2) the reporting system affects the performance accountability of Baubau City government agencies, with a significance value of 0.000 <0.05; and (3) budget target clarity and reporting systems simultaneously affect the performance accountability of Baubau City government agencies